2022
DOI: 10.55877/cc.vol7.231
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Social and Economic Impact of Large Scale Cultural Events: A Social Network Analysis

Abstract: Organisation of large scale or mega cultural events requires not only skilful managerial techniques, but also an integrated evaluation approach taking into account such aspects as the cultural, economic, social, political, and environmental context. Mega cultural events can be characterised by complex objectives, diverse funding sources (EU, public, private), a multilayer structure of planned results and effects. All that obviously encumbers evaluation of mega events. The initiative of the European Capital of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…These relationships within a social network can encompass personal connections, professional affiliations, the exchange of resources (such as information, goods, or money), interactions, and more [Tabassum 2018]. SNA represents a perspective, paradigm, or framework, rather than a theory or a methodology [Laķe, Tjarve & Grīnberga 2015]. It is founded on the premise that social life primarily emerges from relationships and the patterns they create.…”
Section: Social Network Analysis In Measuring the Ecosystemmentioning
confidence: 99%
See 1 more Smart Citation
“…These relationships within a social network can encompass personal connections, professional affiliations, the exchange of resources (such as information, goods, or money), interactions, and more [Tabassum 2018]. SNA represents a perspective, paradigm, or framework, rather than a theory or a methodology [Laķe, Tjarve & Grīnberga 2015]. It is founded on the premise that social life primarily emerges from relationships and the patterns they create.…”
Section: Social Network Analysis In Measuring the Ecosystemmentioning
confidence: 99%
“…Visualizing a network becomes challenging when dealing with large and complex networks [Scott 2012]. A study conducted by the author of this paper, focusing on the Riga 2014 programme as part of the European Capital of Culture initiative [Laķe, Tjarve & Grīnberga 2015], found that visualization can be beneficial when nodes include their attributes within the network structure. Additionally, it was concluded that supplementary measures are necessary for a thorough analysis of a network structure.…”
Section: Social Network Analysis In Measuring the Ecosystemmentioning
confidence: 99%